FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR DALAM MENANGGAPI DAN MENGEVALUASI INFORMASI DALAM AU - Aris Eddy Sarwono (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
Abstract Environmental audit represent applied environment management appliance by corporate world for the facility of to better management to environmental performance of them. Though environmental audit not yet precisely defined, but consensus which progressively expand to express that a number of audit type reside in under coverage terminology. On the contrary emerge some activity which not precisely mould as environmental audit. Some environmental voluntary order specificly have referred as environmental audit but the order likely less supported by corporate world and seen credibility loss. Process to guarantee environmental audit credibility to enthusiastic stakeholders can be conducted constructively assessment of independent eksternal. environmental Audit unic more lay in subject broadness which come within in course of is the, measurement and various date type differ which is collected, than used technique. Keywords: environmental audit; environmental management system; environmental issue; environmental order; standard; corporate world; stakeholders; auditors financial